Assessing the Quality of a Security Market: A New Approach to Transaction- Cost Measurement - Hasbrouck, Joel (Review of Financial Studies, 1993)
[I discuss a new method for measuring the deviations between actual transaction prices and implicit efficient prices. The approach decomposes security transaction prices into random-walk and stationary components. The random-walk component may be identified with the efficient price. The stationary component, the difference between the efficient price and the actual transaction price, is termed the pricing error. Its dispersion is a natural measure of market quality. I describe practical strategies for estimating these quantities. For a sample of NYSE stocks, the average pricing error standard deviation estimate is roughly 0.33 percent of the stock price. If the pricing error is normally distributed and if it is always a positive cost incurred by the transaction initiators, the corresponding average transaction cost for these traders is 0.26 percent of the stock price. The dispersion of the pricing error is also found to be elevated at the beginning and end of the trading session.]